Age, growth and food habits of four selected cyprinids in Navigation Pool 8 of the Upper Mississippi River - Thiel, Pamela A. (My University, 1977)
The age rate of growth and food habits of four selected cyprinids were determined for specimens collected from Pool 8 of the Upper Mississippi River during the summer of 1975. The following four species were analyzed: spotfin shiner, golden shiner, emerald shiner, and spottail shiner.
Keywords: Fishes, Food; Fishes, Growth; Fishes, Age; Freshwater fishes, Mississippi River